Boron neutron capture therapy as a novel modality of radiotherapy for oral cancer: Principle and antitumor effect. Issue 1 (23rd March 2012) - Yura, Yoshiaki; Fujita, Yusei
Abstract: Radiotherapy is essential for the treatment of oral cancer, especially in advanced cases. There has been marked progress in this field due to the prevalence of intensity‐modified radiation therapy and introduction of particle radiotherapy using protons and carbon‐ions. However, these treatments are still non‐selective. Boron neutron capture therapy (BNCT) is a unique modality in which neutron beams destroy only boron compound‐bearing tumor cells while leaving the surrounding normal tissues intact. Thus, BNCT is a selective form of radiotherapy, if high tumor/normal tissue ratio in boron concentration could be achieved. The principle of BNCT, and the basic study of the mechanism by which BNCT exerts antitumor effects using oral squamous cell carcinoma (SCC) cells and oral SCC xenografts in mice are described.